Initiation of TNF inhibitor therapy and change in physiologic measures in psoriasis. (7th November 2013) - Wu, J.J.; Liu, L.; Asgari, M.M.; Curtis, J.R.; Harrold, L.; Salman, C.; Herrinton, L.J.
Abstract Background Psoriasis may predispose to cardiovascular disease and diabetes. However, the role of tumor necrosis factor (TNF) inhibitor in mediating this risk is controversial. Objective To assess this relationship, we estimated change in metabolic physiologic measures before and after initiation of TNF inhibitor therapy compared with methotrexate (MTX) therapy among psoriasis patients. Methods We conducted a retrospective cohort study, 2007–2012, using computerized clinical data for 1274 new users of TNF inhibitor and 979 new users of MTX therapy to compare change in blood pressure, lipids, triglycerides, fasting plasma glucose and body mass index (BMI) before and after start of TNF inhibitors or MTX. The study was restricted to new users. We computed within‐person change in each measure, so that each patient served as their own control. In addition, we compared TNF inhibitor patients to MTX patients, by computing the adjusted difference in their group means. In secondary analyses, we examined phototherapy as a comparator. Results Among starters of TNF inhibitor and MTX therapy, within‐person change in physiologic measures at 6 months did not differ significantly. We observed no important or significant changes in any of the physiologic measures with initiation of TNF inhibitor compared with MTX. The same results were found in subgroup analyses focused on men, and on those with hypertension, diabetes mellitus, or obesity. The same results were observed with phototherapy, except that diastolic blood pressure declined by 0.6 mmHg within person during the 6 months after starting phototherapy (P < 0.05). Conclusions The study provides no evidence for improvement of physiologic measures associated with the metabolic syndrome resulting from TNF inhibitor use for psoriasis.